Impact of forest fire on radial growth of tree rings and their element concentrations of Pinus sylvestris and Larix gmelinii in northern China - Wei, Mao; Guo, Xinbin; Ma, Yuanfan; Tigabu, Mulualem; Zheng, Wenxia; Liu, Mengxia; Guo, Futao (Frontiers in Forests and Global Change, 2023)
Through analyzing the responses of the radial growth and element concentrations (B, Mg, Al, K, Ca, Mn, Fe, Zn, Na, P, Ni, and Cu) of tree rings of two dominant tree species to forest fires, we aimed to investigate the relationship between tree rings and the fires. We sampled wood cores of Pinus sylvestris and Larix gmelinii in the northern forest region of China, where forest fires happened in 1990 and 2008. The ring-width growth of P. sylvestris and L. gmelinii from 1986 to 1995 and 2004 to 2013 in two sites of Tahe County were measured. Element concentrations in tree rings were determined using inductively coupled plasma mass spectrometry (ICP-MS). Our results showed that tree-ring radial growth was largely reduced after the fire, together with the increase in concentrations of B, Al, Mn and Fe but the decrease in some samples in K. Strong correlations were observed between tree-ring growth and concentrations of Mg and Mn of P. sylvestris and Znof L. gmelinii. The results provide evidence that variations in tree-ring growth and element concentrations, particularly concentrations of B, Al, Mn, and Fe, are potentially useful to monitor forest fires, which add new insights into the study of forest fire history.